Study on Seismic Response and Damping Measures of Surrounding Rock and Secondary Lining of Deep Tunnel - Baoli Tang; Yongqiang Ren (Shock and Vibration)
Tunnel construction is gradually developing to areas with high in situ stress; the deeper the tunnel construction, the more intense the earthquake disturbance. Under the background of frequent earthquakes, the seismic characteristics of tunnels become an important content related to the safety and stability of engineering structures. In view of the key problems of seismic response and vibration reduction measures for complex deep buried tunnels, the methods of advanced grouting and foam concrete aseismic are studied in this paper. Firstly, through geological survey, the in situ stress and geological conditions of the study area are analyzed. The structural characteristics of surrounding rock and related rock mechanics parameters are analyzed. The failure criterion of concrete lining under dynamic load is studied theoretically, and the relevant numerical calculation parameters are modified. A numerical model based on viscous boundary conditions is established. Through numerical calculation, the seismic response of tunnel surrounding rock and lining under different damping measures is analyzed. The research results have theoretical research value and social and economic benefits for ensuring the safety and stability of tunnel structure and improving the seismic fortification level.